(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article is dedicated to research of metaphor in language creativity of Ukrainian poets-«neoclassics». In the article is defineted stylistics functions and structure feature of metaphor. The indensios of individual word using are trasing in the language creatavity of «neoclassic».